2021
DOI: 10.1111/nicc.12683
|View full text |Cite
|
Sign up to set email alerts
|

The family intensive care unit syndrome: A qualitative content analysis

Abstract: Background: Hospitalization of patients in an intensive care unit (ICU) is associated with a series of psychological problems for their family members called family intensive care unit syndrome (FICUS). Nonetheless, family members of patients in ICU often receive little attention from health care providers. Exploring family members' experiences of their patients' hospitalization in ICU helps health care providers focus more clearly on their problems.Aims and objectives: This study aimed to explore FICUS-relate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 37 publications
0
15
0
1
Order By: Relevance
“…They are subjected to high levels of psychological stress due to adverse events during the IHT. As a result, many negative emotions are generated (Karlsson et al, 2020), not only does it damage their own psychological, physical and social relationships but it also leads to decision-making disorders that affect patients' treatment and disease prognosis (Saeid et al, 2020(Saeid et al, , 2022. Psychological problems for the patient's family members can range from severe negative emotions on admission to the ICU to decreased quality of life over time.…”
Section: Backg Rou N Dmentioning
confidence: 99%
“…They are subjected to high levels of psychological stress due to adverse events during the IHT. As a result, many negative emotions are generated (Karlsson et al, 2020), not only does it damage their own psychological, physical and social relationships but it also leads to decision-making disorders that affect patients' treatment and disease prognosis (Saeid et al, 2020(Saeid et al, , 2022. Psychological problems for the patient's family members can range from severe negative emotions on admission to the ICU to decreased quality of life over time.…”
Section: Backg Rou N Dmentioning
confidence: 99%
“…In the integrative literature review, FICUS-related instruments were reviewed and their items were used to generate the FICUSI items. The results of the review and the qualitative study, published elsewhere (Saeid et al, 2020(Saeid et al, , 2022. First, 144 items were designed based on the findings obtained from the literature review and the qualitative study.…”
Section: Phase 1 Ficusi Developmentmentioning
confidence: 99%
“…Recent studies highlighted that FICUS includes not only psychological problems but also physical, spiritual, and social problems (Saeid et al, 2020(Saeid et al, , 2021. Therefore, FICUS can be a threat to the physical, psychological, spiritual, and social health of the family members of patients in ICU (Saeid et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…5 After recognizing the psychological repercussions of the closest family members of dying ICU patients, patient-centered care rather than clinician-or disease-centered care, based on the view that not only the patients being treated but also their relatives have some needs, has gained prominence. [6][7][8][9][10] Previous studies indicated that at least two-thirds of the family members of ICU patients experience anxiety or depression symptoms during the ICU period. 2 It has been reported that these symptoms can be affected by age, gender, education level, relationship, and disease severity.…”
Section: Introductionmentioning
confidence: 99%